E-shoppers and multimodal accessibility to in-store retail: An analysis of spatial and social effects - Mateos-Mínguez, Paloma; Arranz-López, Aldo; Soria-Lara, Julio A.; Lanzendorf, Martin (Journal of transport geography, 2021)
Amidst the growing interest in enhancing the academic understanding of the relationships between e-shopping and transport, a key element remains underexplored – the impact of e-shopping on spatial accessibility to in-store retail. The paper studies variations in multimodal accessibility to in-store retail between e-shopper groups and the associated spatial effects. The research is based on a face-to-face questionnaire, administered in the city of Alcalá de Henares (Madrid Metropolitan Area, Spain), which provides data on socio-economic characteristics, e-shopping habits, and travel time preferences to reach in-store retail. Clustering techniques serve to identify three e-shopper groups: occasional e-shoppers with a car, infrequent e-shoppers with a car, and frequent e-shoppers without a car. A comparison of e-shopper distance-decay functions to reach in-store retail is made, revealing significant differences between the three e-shopper groups for car and public transport for any time interval. However, for walking such differences are limited to time intervals between 10 and 40 min. Distance-decay functions are processed through a gravity-based model, identifying five categories of multimodal accessibility places that provide information on how in-store retail locations may be affected by e-shopping habits. The paper closes with concluding remarks on policy-making and a few pathways for future research.